Pengaruh Beban Kerja Terhadap Kinerja Kurir Shopee Express Hub Cikampek - Dicky Sulistiya Harta Wijaya; Enjang Suherman; Laras Ratu Khalida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine and analyze the effect of workload on the performance of Shopee Express Hub Cikampek couriers. The method used is a quantitative descriptive verification method which aims to describe whether or not the facts are true, and to explain the relationship between workload variables and Shopee courier performance. The sample in this study was 85 people from 113 populations, the analysis technique used was a simple linear regression analysis technique using SPSS version 25. The results of the research data processing stated that workload had a positive effect on the performance of Shopee Express Hub Cikampek couriers. The results of the study are proven by the results of hypothesis testing which show that the calculated t value is greater than the t table and the significance value is smaller than alpha. Based on the results of the analysis in this study, it was also found that workload has a strong relationship with the performance of Shopee Express Hub Cikampek couriers, where workload contributes a positive influence on performance with a value of 42.7%.